DETERMINAN PARTISIPASI PENGANGGARAN DAN PENGARUHNYA TERHADAP KINERJA MANAJERIAL APARAT PEMERINTAH DAERAH KABUPATEN BANYUMAS - Wahyuningsih, Sulung; Pramuka, Bambang Agus (JURNAL AKUNTANSI DAN AUDITING, 2012)
This study analyzed the effect of work attitudes, need for achievement, locus of control, anddecentralization on managerial performance of local government officers, with the budgetaryparticipation as an intervening variable, which was developed from the study of Din (2008). Datawas obtained from 115 SKPD officials of Banyumas regency using purposive sampling methodthrough questionnaires. Data analysis was performed with the Structural Equation Model (SEM).The results of this study indicated that there was no significant effect of work attitude on thebudgetary participation, but it has positive and significant direct impact on managerialperformance of local government officers. The need for achievement had a positive and significantimpact on budgetary participation, but it does not directly affect managerial performance of localgovernment officers. Locus of control did not have significant influence to the budgetaryparticipation and managerial performance of local government officers. Decentralization hadpositive and significant impact on budgetary participation and managerial performance of localgovernment officers. Budgetary participation has positive and significant impact on managerialperformance of local government officers. Budgetary participation was only mediating the effect ofneed for achievement on managerial performance of local government officers.Keywords:work attitude, need for achievement, locus of control, decentralization, participationbudgeting, managerial performance, banyumas local government officials,